A Skin-Inspired Self-Adaptive System for Temperature Control During Dynamic Wound Healing - Yaqi Geng; Guoyin Chen; Ran Cao; Hongmei Dai; Zexu Hu; Senlong Yu; Le Wang; Liping Zhu; Hengxue Xiang; Meifang Zhu (Nano-Micro Letters, 2024)
Highlights An interactive electronic system inspired by the temperature self-regulation of human skin. Heat stimulation therapy and temperature monitoring during dynamic wound healing. Mechanism of temperature self-regulation during dynamic wound healing.